Locating experts and carving out the state of the art: A systematic review on Industry 4.0 and energy system analysis. (14th March 2019) - Nolting, Lars; Kies, Alexander; Schönegge, Marius; Robinius, Martin; Praktiknjo, Aaron
Summary: As Germany's manufacturing industry highly depends on international competitiveness, German companies must rapidly assimilate to current processes of digitization and so‐called Industry 4.0. These processes will also affect the German energy system. Understanding and predicting the implications of these changes is one of the core elements of energy system analysis. To address this issue, herein, we present a structured and systematic review of literature within the intersection of industrial digitalization in the sense of Industry 4.0 and scientific energy system analysis. The goals of this study are (1) to reveal the locations and institutions of relevant experts and (2) to carve out the current state of the art with regard to technologies that enable (digitized) industries to interact with the energy system in order to contribute to a smart energy system. Our approach is based on a systematic and reproducible keyword search using the scientific literature database Scopus. Both a quantitative evaluation and a qualitative evaluation of the relevant literature are conducted. The quantitative results are presented using GIS‐based visualizations. This facilitates us to identify the European Union as main contributor on a global level and the United Kingdom as the most prolifically publishing country within the European Union. Focusing on Germany, we find North Rhine‐Westphalia to be the most scientifically active area and Aachen/Dortmund to be the cities where most publications originate. In the qualitative, content‐based part of this review, we show that in particular sector coupling and the integration of distributed energy prosumers can lead to a working smart energy system. We demonstrate that industrial digitalization processes in the sense of Industry 4.0 can serve as enabling factor in this respect. Further, we provide extensive summaries regarding both the technological and economic potentials and challenges of different technologies in future smart energy systems. Taking all of the results into account, we outline a framework to connect the highly discussed topics of digitalized industries and smart energy systems to corresponding experts. Abstract : We present a structured and systematic review of literature within the intersection of industrial digitization in the sense of Industry 4.0 and scientific energy system analysis. Within our study, we (1) reveal the locations and institutions of relevant experts and (2) carve out the current state of the art with regard to the technological and economic potential of different technologies that enable (digitized) industries to interact with the energy system in order to contribute to a smart energy system.